Inhibition of bacterial and human zinc-metalloproteases by bisphosphonate- and catechol-containing compounds. (1st January 2021) - Rahman, Fatema; Nguyen, Tra-Mi; Adekoya, Olayiwola A; Campestre, Cristina; Tortorella, Paolo; Sylte, Ingebrigt; Winberg, Jan-Olof
Abstract: Compounds containg catechol or bisphosphonate were tested as inhibitors of the zinc metalloproteases, thermolysin (TLN), pseudolysin (PLN) and aureolysin (ALN) which are bacterial virulence factors, and the human matrix metalloproteases MMP-9 and −14. Inhibition of virulence is a putative strategy in the development of antibacterial drugs, but the inhibitors should not interfere with human enzymes. Docking indicated that the inhibitors bound MMP-9 and MMP-14 with the phenyl, biphenyl, chlorophenyl, nitrophenyl or methoxyphenyl ringsystem in the S1 ′-subpocket, while these ringsystems entered the S2 ′- or S1 -subpockets or a region involving amino acids in the S1 ′- and S2 ′-subpockets of the bacterial enzymes. An arginine conserved among the bacterial enzymes seemed to hinder entrance deeply into the S1 ′-subpocket. Only the bisphosphonate containing compound RC2 bound stronger to PLN and TLN than to MMP-9 and MMP-14. Docking indicated that the reason was that the conserved arginine (R203 in TLN and R198 in PLN) interacts with phosphate groups of RC2. Graphical Abstract: